Study on risk factors for surgical wound infection in mothers undergoing cesarean sections at a teaching hospital of reference. - Roberta Maia de Castro Romanelli; Regina Amélia Lopes Pessoa de Aguiar; Henrique Vitor Leite; Evilane do Carmo Patrício; Klaus Zanuncio Protil; Andre Tunes de Paula; Lucas Vieira Rodrigues; Bruna Barbosa Coimbra; Letícia Maria de Oliveira Aleixo Carvalho; Lenize Adriana de Jesus; Guilherme Augusto Armond; Wanessa Trindade Clemente (Universidade de Santa Cruz do Sul, 2014)
Backgound and Objectives: Surgical wound infections (SWI) postoperative complications are common and present significant morbidity and mortality with increased time and cost of hospitalization, especially for women undergoing cesarean delivery. Therefore, the aim of this study was to evaluate risk factors for IFC in the reference in high-risk pregnancies from public Belo Horizonte. Methods: A cohort study performed in a referral Maternity - HC / UFMG, 2011-2012, with notification of SWI by active surveillance. All patients undergoing cesarean section were included and telephone contact was performed up to 30 days postpartum. The database was entered in the Statistical Package for Social Sciences. Results: We identified 708 women undergoing cesarean section and telephone contact was achieved with 487 of them during postpartum period. In 14 cases criteria for diagnosis of SWI was full filled (2.9% rate). When comparing groups of women with and without SWI, only the number of digital vaginal examination (≥ 2) was statistically significant for SWI cases. Conclusion: In the case of IFC, the average of digital vaginal examination was below reported in literature. It is emphasized that the procedure should be performed when absolutely necessary, respecting the rules of asepsis. KEYWORDS: Cesarean section. Surgical wound infection. Epidemiological surveillance. Diseases notification. Postpartum period.